Nickel‐Catalyzed N‐Arylation of NH‐Sulfoximines with Aryl Halides via Paired Electrolysis. (17th March 2021) - Liu, Dong; Liu, Zhao‐Ran; Ma, Cong; Jiao, Ke‐Jin; Sun, Bing; Wei, Lei; Lefranc, Julien; Herbert, Simon; Mei, Tian‐Sheng
Abstract: A novel strategy for the N‐arylation of NH‐sulfoximines has been developed by merging nickel catalysis and electrochemistry (in an undivided cell), thereby providing a practical method for the construction of sulfoximine derivatives. Paired electrolysis is employed in this protocol, so a sacrificial anode is not required. Owing to the mild reaction conditions, excellent functional group tolerance and yield are achieved. A preliminary mechanistic study indicates that the anodic oxidation of a Ni II species is crucial to promote the reductive elimination of a C−N bond from the resulting Ni III species at room temperature. Abstract : A novel strategy for the N ‐arylation of NH ‐sulfoximines has been developed by merging nickel catalysis and electrochemistry (in an undivided cell), thereby providing a practical method for the synthesis of sulfoximine derivatives. Paired electrolysis is employed in this protocol, so a sacrificial anode is not required.